آیاتِ لعان:احکام القرآن (تھانوی) اور تفسیر نمونہ کی روشنی میں تجزیاتی مطالعہ (Al-Qamar, 2022)
life, provides intensive injunctions on marital life. It proposes reverence to scrupulousness of spouses. Unjustified blaming on someone causes anarchism and brings dishonor. Accusing someone of immorality or illicit affair without any Shar'i evidence is haraam and a grave sin, and if a woman is chaste, the sin of slandering her is more severe than slandering an ordinary person, if the husband accuses his wife of adultery. So in the presence of the Shariah court there will be "Lian". The term Lian (Execration) refers to the testimony of God's curse and wrath on behalf of each of the spouses with an oath. This curse substitutes the false accusation in favor of the husband and the of penance of depravity (Shariah punishment) in favor of the wife. Quran has offered admirable rulings in the verses of Lian to shield the rectitude of spouses. Using qualitative research method, this article has made an attempt to analyses the rulings about Lian in the light of Ahkam-ul-Quran and Tafsir-e-Namoona.
Keywords: Lian; rulings; Ahkam-ul-Quran; Tafsīr-e-Namoona